THE EFFECT OF FINANCIAL LITERACY, RISK TOLERANCE, OVERCONFIDANCE AND INCOME ON INVESTMENT DECISIONS (Case Study on Financial Management Students of Universitas Pelita Bangsa Class of 2019 - Dela Fadilah; Siska Wulandari (Universitas Islam Lamongan, 2023)
The purpose of this study is to determine the effect of Financial Literacy, Risk Tolerance, Overconfidance and Income on Investment Decisions. The research method used is quantitative. The data collection technique used is a questionnaire. In this study used Isaac and Michael's table to determine a sample of 143 respondents. The analysis methods used are validity tests, reliability tests, classical assumption tests, multiple linear regression tests, hypothesis tests and determination coefficient tests. With the help of SPSS version 23 as a test tool. The results showed that the validity and reliability of all questions from the questionnaire fell into categories, the results of the coefficient of determination obtained were 0.790 or 79%, the results of the hypothesis test showed that Financial Literacy, Risk Tolerance, Overconfidance and Income partially had a significant effect on Investment Decisions in Financial Management Students of Pelita Bangsa University class of 2019. Keywords : Financial Literacy, Risk Tolerance, Overconfidance, Income, Investment Decisions.